2015
DOI: 10.1002/etc.2881
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the influence of physicochemical properties on gold nanoparticle uptake and elimination by Daphnia magna

Abstract: Monitoring the distribution and subsequent effects of nanoparticle contaminants in aquatic ecosystems will be pivotal to developing regulations that minimize their environmental footprint. The present study focused on the link between nanoparticle characteristics and Daphnia magna body burden using gold nanoparticles (AuNPs) with different size, shape, and surface charge configurations as model particles. Uptake followed first-order kinetics across the entire concentration range for all particles except the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…However, TiO 2 NPs were shown to be bioaccumulative in D. magna in another kinetic modeling study in which the BCFs ranged from 2.40 Â 10 5 to 1.52 Â 10 6 L/kg. Our predicted BCF values for D. magna were also analogous to those predicted by others (Wray and Klaine 2015), who have implemented a similar kinetic approach producing BCF values ranging from 1460 to 47 700 L/kg in the same species. Our predicted BCF values for D. magna were also analogous to those predicted by others (Wray and Klaine 2015), who have implemented a similar kinetic approach producing BCF values ranging from 1460 to 47 700 L/kg in the same species.…”
Section: Applicability Of Kinetic Models To Predict the Bioaccumulatisupporting
confidence: 85%
“…However, TiO 2 NPs were shown to be bioaccumulative in D. magna in another kinetic modeling study in which the BCFs ranged from 2.40 Â 10 5 to 1.52 Â 10 6 L/kg. Our predicted BCF values for D. magna were also analogous to those predicted by others (Wray and Klaine 2015), who have implemented a similar kinetic approach producing BCF values ranging from 1460 to 47 700 L/kg in the same species. Our predicted BCF values for D. magna were also analogous to those predicted by others (Wray and Klaine 2015), who have implemented a similar kinetic approach producing BCF values ranging from 1460 to 47 700 L/kg in the same species.…”
Section: Applicability Of Kinetic Models To Predict the Bioaccumulatisupporting
confidence: 85%
“…However, absorption of nanomaterials by daphnids into tissues other than the gut tract has been observed for quantum dots 78 , carboxylated polystyrene beads 79 , and silver nanowires 80 . It is important to point out that a larger number of studies have not identified absorption of nanomaterials through the GI tract and into other tissues by daphnids: quantum dots 81 , fullerenes 82 , and gold nanoparticles 83, 84 . It is currently unclear why absorption into systemic circulation is observed in some studies but not others for tests with similar nanomaterials (e.g., quantum dots).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, NMs do not readily pass through the epithelial tissues in the gut tract or the surface skin [33], or may be slower to absorb compared with solutes, so further work on the time scales of such tests will be needed. Wray and Klaine [34] examined the influence of particle characteristics (AuNP surface charge, size, and shape) on total body burden in D. magna and found no evidence that AuNPs were absorbed across epithelial membranes, a result similar to other studies with carbon nanomaterial [23,35,36]. These authors discuss the possibility that a part of the ingested NPs may adsorb to gut structures (e.g., microvilli) and that these have a slower transport out of the gut compared with NPs that are not in contact with gut structures.…”
Section: Confirmation Of Exposure Through Body Burden Assessmentmentioning
confidence: 99%